Fighting Patent Trolls Early: Learning from the United Kingdom in Our Scramble to Determine the Correct Pleading Standards for Direct Patent Infringement - Adam Copeland (Washington University Global Studies Law Review, 2022)
Congress, since the time of the country’s founding, has sought to “promote the [p]rogress of [s]cience and useful [a]rts” through the patent system. Yet the progress of science and useful arts has been hampered recently, ironically through the patent system that was designed for their promotion. This is because patent holders who produce no goods (also known as non-practicing entities—or, pejoratively, “patent trolls”) have taken to leveraging vague patents against true innovators through expensive litigation in hopes of spurring these innovators to settle the case. This leaves one to wonder: how did these frivolous claims become so lucrative? To answer this, one must delve into the historical development of pleading standards in the United States. Plaintiffs formerly enjoyed a lax pleading standard that only required minimally coherent facts. However, by the beginning of the twenty-first century, these “notice pleading” standards evolved to become far less pro-plaintiff. Litigants pleading direct patent infringement initially enjoyed insulation from these newly heightened standards through Federal Rule of Civil Procedure 84, which permitted them to initiate a claim with a brief, boilerplate, non-fact-intensive form. However, this Rule was abrogated in 2015, leaving district courts to wonder how one was to plead direct patent infringement in light of the new heightened pleading standard. A more pro-plaintiff standard would make it easier for patent trolls to file frivolous lawsuits; a less pro-plaintiff standard would make it harder for patent owners to fully enforce their rights. This note considers whether the United States might benefit from a strict pleading standard for direct infringement by comparing its pleading standard to that of the United Kingdom. While the data available on patent trolls in the United Kingdom is unfortunately sparse, the discrepancy in the prevalence of patent trolls between the two countries might indicate that a stricter pleading standard like that in the United Kingdom might help the United States in its fight against patent trolls. The tools the United Kingdom uses to help safeguard its patent system and inventors from patent trolls—e.g., high administrative costs to obtain a patent and the “loser pays” rule—indicate that patent trolls are cost-conscious; when litigation presents financially high risks, they will abandon the plan to bring suit. Therefore, it is reasonable to deduce that the United Kingdom’s higher pleading standard for patent infringement performs the same function, and thus the United States could benefit from a similar standard.